Long Non-Coding RNA SNHG1 Regulates the Wnt/β-Catenin and PI3K/AKT/mTOR Signaling Pathways via EZH2 to Affect the Proliferation, Apoptosis, and Autophagy of Prostate Cancer Cell - Chen, Junyi; Wang, Fubo; Xu, Huan; Xu, Lingfan; Chen, Dong; Wang, Jialiang; Huang, Sihuai; Wen, Yiqun; Fang, Longmin (Frontiers in Oncology, 2020)
Prostate cancer (PCa) is the most common malignant cancer in western developed countries, which has seriously threatened the life style and quality of life of men. The pathogenesis and causes of PCa remain indistinct. Currently, it was found that the small nucleolar RNA host gene 1 (SNHG1) of long non-coding RNA (lncRNA) is highly expressed in multiple tumors and exerts proto-oncogene effect, but its function and mechanism in PCa have not been studied. PCa cells LNCaP, PC-3, DU-145 in logarithmic phase were transiently transfected with Lipofectamine3000 into control plasmid, small interfering RNA plasmid (si-SNHG1) and si-SNHG1+multicellular protein EZH2 small interfering RNA plasmid (si-EZH2), respectively. The lncRNA-SNHG1 and EZH2 mRNA in the cells were detected by Real-time PCR; the EZH2 protein, Wnt/β-catenin and PI3K/AKT/mTOR signaling pathway related protein expression in the cells were detected by Western blotting; LC3 spot formation was detected by immunofluorescence; the proliferation ability of cultured cells was observed by MTT method; and the viability and apoptosis degree of the cells were observed by cell colony and flow cytometry respectively. RT-PCR results confirmed that SNHG1 was up-regulated in PCa tissues and cells. Among PCa cells, interfering SNHG1 inhibited proliferation, promoted apoptosis and autophagy of PCa cells. RNA Pull down and RNA IP experiments demonstrated that SNHG1 binds to EZH2. Compared with the control group, after interfering SNHG1 or EZH2, the cell proliferation and activity in PCa cells decreased significantly, cell apoptosis and autophagy increased significantly, and the related proteins of Wnt/β-catenin and PI3K/AKT/mTOR signaling pathways decreased significantly. However, after interfering with SNHG1 and overexpressing EZH2, the results are just the opposite. This study revealed that lncRNA-SNHG1 regulates Wnt/β-catenin and PI3K/AKT/mTOR signaling pathways through EZH2 gene to affect proliferation, apoptosis and autophagy of PCa cells. This experiment provides ideas and experimental basis for treating PCa patients and improving therapeutic effect.